IDEOLOGI DAN POPULAR CULTURE - Priyatna, Endang Suryana (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2012)
During New Order Regime (Orba) in Indonesia, Pancasila was conceptualized and internalized as the state and national ideology. However, the regime turned it into a state control ideology, legitimizing repressive act conducted by the state. Nowadays, in the period of post new order regime, the calls to return to the reconceptualization and reinternalization of Pancasila seem to be very immanent. At least, that is what can be inferred and interpreted from the speech given by four national leaders during the commemoration of the birth of Pancasila in 1 June 2011. This essay tries to analyze how the ideas of reconceptualization of Pancasila as state ideology are conferred in the speech. By relating the speech to certain discursive formations surrounding Pancasila and recent cultural phenomenon and practices in Indonesian public sphere, the essay tries to contest the validity of such conceptualizations. The result shows that Pancasila as state ideology seems to be irrelevant and obscured in the cultural practices and activities of the public. It shows that Pancasila resides at the heart of the political elites, but not inside the everyday life